SOSIALISASI PENCEGAHAN STUNTING DI DESA SANDING, KECAMATAN PETIR, KABUPATEN SERANG BANTEN (Socialization Of Stunting Prevention in Sanding Village, Petir District, Serang Banten) - Elvina Nuryadin, Devi Faustine (Universitas Sultan Ageng Tirtayasa, 2023)
The problem of failure to thrive in children due to insufficient nutritional intake over a verylong period of time will cause a problem known as stunting. The problem of stunting is a chronicproblem that has become a concern for the Indonesian government. Socialization to provideinformation to the community, especially in Sanding Village, Petir District, Serang-Banten, isneeded in efforts to prevent stunting. It is hoped that with socialization, the community, especiallythose who become parents, can increase their role in monitoring the growth and development oftheir children. This community service activity was carried out in Sanding Village, Petir District,Serang Banten in February 2023 by giving questionnaires (pre-test and post-test) to thecommunity who were participants in the socialization. Participants who attended were 88%housewives with 44% of the most dominant education being junior high school, and 74% fathersworking as laborers with 60% having high school education. During the socialization, 19 (68%)of the participants who came knew what stunting was, but after the socialization, 27 (96%) almostall participants already understood what stunting was. The results of the questionnaire alsoprovided information that the 28 people who attended the socialization activity alreadyunderstood the causes and efforts to prevent stunting.